2015
DOI: 10.1016/j.otsr.2014.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for the recurrence of myxoid liposarcoma: 20 cases with up to 8 years follow-up

Abstract: Prognostic factors for the recurrence of myxoid liposarcomas have been identified. MRI analysis is not definitive and must be supplemented by a biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…Even if diagnosis might be considered sooner due to easier palpation detection by patients, this could not explain such a delay. A potential explanation should be a statistical histological subtype preponderance of clear cell, epithelioid, and synovial sarcomas, which may affect younger patients with a lower incidence in DESTS sarcomas of myxoid liposarcomas and liposarcomas, usually developing in older patients . Histological preponderance might also explain DESTS male patient preponderance and impact on prognosis compared to women .…”
Section: Discussionmentioning
confidence: 99%
“…Even if diagnosis might be considered sooner due to easier palpation detection by patients, this could not explain such a delay. A potential explanation should be a statistical histological subtype preponderance of clear cell, epithelioid, and synovial sarcomas, which may affect younger patients with a lower incidence in DESTS sarcomas of myxoid liposarcomas and liposarcomas, usually developing in older patients . Histological preponderance might also explain DESTS male patient preponderance and impact on prognosis compared to women .…”
Section: Discussionmentioning
confidence: 99%
“…A study including 20 cases of myxoidliposarcoma, found that after a follow up of 8 years, tumors with more than 5 % of round cells had a greater risk of recurrence [26]. Other authors found the same results [27].…”
mentioning
confidence: 72%
“…MLS primarily metastasizes to extrapulmonary sites including bones such as spines and other soft tissues such as retroperitoneum, in contrast to the other subtypes of LP which mainly metastasize to the lung . The percentage of MLS metastasis ranges from 14% to 32%, and its prognostic factors have been previously reported. Factors strongly associated with a poor prognosis include age (>45 years), tumor size (>10 cm), high histological grade, and percentage of round cell differentiation (>5%) .…”
Section: Discussionmentioning
confidence: 96%
“…Factors strongly associated with a poor prognosis include age (>45 years), tumor size (>10 cm), high histological grade, and percentage of round cell differentiation (>5%) . The occurrence of a round cell component is the most significant factor for local recurrence, metastasis, and survival . The risk of local recurrence is 3.4 times greater if a tumor consists of more than 5% round cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation